Bridging the Gap of Green IT/IS and Sustainable Consumption - Kuan-Siew, Khor; Ramayah, Thurasamy; Noor Hazlina, Ahmad; Hasliza, Abdul Halim; Lo, May-Chiun (SAGE Publications, 2015)
‘Greening’ of business has gained attention across industries and academia. Green information technology (IT) is a critical domain of green information systems (IS) as utilization of environmentally sustainable information and communication technologies (ICTs) facilitates informed decision-making. Green IT and IT for green are at the growth stage among developed countries and at the infancy stage among developing countries. The absence of an established theoretical framework that anchors present and future studies necessitates an examination of peer-reviewed journals and proceedings that are published online. With reference to 10 organizational theories, this study presents an overview of Green IT/IS applications and discusses noteworthy research questions that may guide forthcoming empirical investigations to identify determinants or prospective outcomes of Green IT/IS. Frameworks of a firm’s readiness to go green via eco-sustainable IT practices are discussed from diverse theoretical viewpoints to ground implications, in pertinence to heterogeneous approaches towards the adoption of Green IT/IS. The review also presents practical business opportunities to IT managers of socioeconomic- oriented organizations. As journals and conference papers are the foremost source of reference, emerging developments of this study may also appear in books and white papers. This article establishes linkages between organizational theories and Green IT/IS implementations and presents suggestions on further extensions for those who wish to investigate this field.